Minor diterpenoids from Scutellaria galericulata. (March 2016) - Penchev, Plamen N.; Coll, Josep; Nicolova, Katia; Iliev, Ilia N.; Bozov, Petko I.
Graphical abstract: Highlights: Three new neo-clerodane diterpenoids have been isolated from Scutellaria galericulata . Chemical structures of the new compounds were elucidated by spectroscopic techniques. New assignments and corrections of the previously reported NMR signals were included. Abstract: Three new neo-clerodane diterpenoids, one C-16 epimeric pair, scutegalerins C and D, and scutegalerin E, together with the known scutaltisin B, were isolated from the acetone extract of the aerial parts of Scutellaria galericulata . The chemical structures of the new compounds were elucidated by spectroscopic techniques and a comparison with data of similar compounds as (13 S, 16 R, 19 S )-6α-acetoxy-2α, 19;4α, 18;15, 16-triepoxy-16, 19-dimethoxy-neo-clerodane (scutegalerin C), (13 S, 16 S, 19 S )-6α-acetoxy-2α, 19;4α, 18;15, 16-triepoxy-16, 19-dimethoxy-neo-clerodane (scutegalerin D) and (11 S, 13 R, 16 S, 19 S )-6α - acetoxy - 2α, 19;4α, 18;11, 16;15, 16-tetraepoxy-19-methoxy-neo-clerodan-3β-ol (scutegalerin E). Detailed NMR spectra of scutaltisin B were included to rationalize the new assignments in the 1 H NMR spectrum and the correction of some of the previously reported carbon signals in the 13 C NMR spectrum for the isolated mixture of the two C-11 epimers scutaltisin B and scutaltisin C.